Analisis Manajemen Risiko di Daya Tarik Wisata Puncak Koto Panjang Kabupaten Pasaman - Yanti, Efrida; Susanti, Retnaningtyas (Jurnal Kajian Pariwisata Dan Perhotelan, 2024)
This study's motivation stems from the insecurity and safety supervision that causes the risk of danger to visitors near the summit of Pasaman Regency's lengthy koto. This study aimed to examine risk management at the Long Koto tourist attraction's highest point. Qualitative data collected through documentation, interviewing, and observation methods are used in this study. According to the findings, there was virtually little risk at Puncak Koto Panjang.The level of security and safety has a value of 6 with a very low risk level category, the mitigation carried out accepts the risk that is tolerated. Facilities at the top of the long koto require improvement, the severity and opportunity level of risk has a value of 3 with a very low risk level category, the mitigation carried out is to reduce the risk by conducting routine evaluations. The source of danger at the top of Koto Panjang is the danger of vegetation and the danger of the ravine which has a severity level and a risk opportunity level of 10 with a low risk level category, the mitigation carried out accepts the risks that occur.